2021
DOI: 10.1177/13654802211021756
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising inclusive education in Saudi Arabia through conversations with special education teachers

Abstract: In the last decade, inclusive education (IE) has become a trending topic in the Kingdom of Saudi Arabia. This small-scale, qualitative Saudi study reports on how some teachers view IE in their country and whether students with a disability (autism) could be educated in mainstream schools. Individual semi-structured interviews were conducted and recorded using a smartphone. The analysis of interview data identified three themes related to IE and the concept of mainstream schooling for students with autism. Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
8
0
2
Order By: Relevance
“…The provision of educational services and social support for students with special needs has seen tremendous growth in the last 20 years (Alnahdi et al, 2019; Gibbs & Bozaid, 2022). Coupled with increased support is the promotion of inclusive education for students with SEND by the Ministry of Education.…”
Section: Inclusive Education In Saudi Arabiamentioning
confidence: 99%
See 2 more Smart Citations
“…The provision of educational services and social support for students with special needs has seen tremendous growth in the last 20 years (Alnahdi et al, 2019; Gibbs & Bozaid, 2022). Coupled with increased support is the promotion of inclusive education for students with SEND by the Ministry of Education.…”
Section: Inclusive Education In Saudi Arabiamentioning
confidence: 99%
“…Another author identified that inclusive education in Saudi Arabia is challenged by inadequate physical and human support coupled with poorly organized school structure and culture (Alruwaili, 2018). A recent Saudi study described the Saudi Arabia education system as gender-segregated (Gibbs & Bozaid, 2022). These authors concluded that “for many students with a disability, participation in Saudi mainstream classrooms remains allusive” (Gibbs & Bozaid, 2022, p. 4).…”
Section: Challenges Of Inclusive Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Without a Special Assistant Teacher, if there is a problem for students with special needs, the class teacher is not able to overcome it, in the end, the teacher will teach according to what he knows. Gibbs and Bozaid (2021), so it does not make it if the general education teacher feels less ready to serve students with special needs, because they have not received the training needed to develop skills for students with special needs.…”
Section: Sdn 14 Payakumbuhmentioning
confidence: 99%
“…There are French theories that intellectual ability is not part of educational inclusion, this examines the variation of the type of ability of students in their way of communication, motor function, sensory function and even in their way of learning, which has to demonstrate social attitudes of educational inclusion [14], while in Arabic countries students with autism abilities have to attend regular schools as normal, because teachers teach these young people after achieving special trainings on the subject [15], in order to achieve a well-defined paradigm on educational inclusion in all types of educational institutions whether public, private, rural or urban, management will is needed [16] to share and/or collaborate among teachers the keys of how to implement educational inclusion within the classroom, the institution and the locality [17].…”
Section: Introductionmentioning
confidence: 99%